Quantum effects in gravitation and gravitational analogues - de Paula, Lucas Tobias; Spadin Domingues, Murillo; Richartz, Maurício (Cadernos de Astronomia, 2025)
Modern physics reveals that the quantum vacuum, far from being an absolutely empty space, exhibits peculiar properties when analyzed in a curved spacetime, such as in the vicinity of black holes. The interaction between quantum fields and spacetime geometry is formally described by Quantum Field Theory in Curved Spacetimes, which treats gravitational effects as classical manifestations of spacetime curvature, as established by General Relativity. Hawking radiation, for instance, describes how quantum fluctuations near a black hole lead to thermal emission to the exterior, resulting in its gradual evaporation. Another example is the Unruh effect, which predicts that an accelerated observer perceives a thermal bath of radiation in a region where an inertial observer would see only the particle vacuum. However, these phenomena are difficult to detect directly due to the extreme scales involved, which result in thermal emissions of extremely low temperatures. To overcome this limitation, scientists have developed analogue models of gravity. These analogue models are systems (for example, fluid flows and ultracold gases) that reproduce, in the laboratory, conditions equivalent to curved spacetimes. Experiments based on these models allow us to study how spacetime structure influences the quantum behavior of the vacuum, bridging theory and observation and deepening our understanding of the interface between gravity and quantum mechanics.